Exploring the Components of Subjective Well-Being Among Individuals Living in Urban Stressful Environments - Yang, Jiantang; Mehdiabadi , Parichehr; Kröger , Anni (KMAN Counseling & Psychology Nexus, 2025)
The aim of this study was to explore the psychological, social, and environmental components of subjective well-being among individuals residing in stressful urban environments in the United Kingdom. This qualitative study employed an exploratory design to capture participants’ lived experiences of well-being in the context of urban stress. A purposive sampling strategy was used to recruit 28 adults living in metropolitan and mid-sized urban areas across the United Kingdom. Semi-structured interviews were conducted until theoretical saturation was reached, focusing on coping strategies, sources of support, and perceptions of well-being. Each interview lasted between 45 and 70 minutes, was audio-recorded with consent, and subsequently transcribed verbatim. Data were analyzed using thematic analysis supported by NVivo 14 software. Reflexive memoing and iterative coding were employed to ensure rigor, and Braun and Clarke’s six-phase approach guided the analytical process. Analysis revealed three overarching themes shaping subjective well-being: (1) psychological and emotional well-being, which included coping with stress, resilience, emotional regulation, and challenges such as anxiety and burnout; (2) social and relational well-being, encompassing family support, friendships, workplace relations, and community belonging, alongside the negative impact of social isolation; and (3) environmental and lifestyle well-being, which included access to green spaces, urban infrastructure, financial stability, safety, cultural participation, and technology use. Participants emphasized the protective role of resilience, social support, and access to restorative environments, while highlighting financial insecurity, social isolation, and digital overuse as key threats to well-being. Subjective well-being in urban stressful environments is a multidimensional construct shaped by individual coping strategies, social support systems, and environmental conditions. Strengthening resilience, enhancing community connectedness, and addressing structural urban challenges are essential for promoting healthier, more sustainable urban living.